the answer is: (y-b)/x = m y = mx + b y - b = mx (y-b)/x = m
m stands for modulus.
x = (y-b)/m
If y = mx + b, then x = (y-b)/m (for m not equal to zero).
The slope and y intercept which are m and b respectively.
It is the equation of a straight line
Y=mx+b. first you subtract b from both sides of the equation. Y-b=mx then you divide m from both sides because x is being multiplied by m. so then you get (y-b)/m=x and that's your answer
y = mx + bAt the x-intercept, y = 0 :0 = mx + bSubtract b from each side of the equation :-b = mxDivide each side by 'm' :-b/m = x
The equation y = mx + b is the equation for a line in slope-intercept form. The slope is m, and the y-axis intercept is b.
m is the slope of the line; that is, the change in y divided by the change in x
The graph of the equation is a straight line. 'm' is its slope. 'b' is its y-intercept
The x in y=mx+b is the independent variable. You could solve for x, making this a function of y, with simple algebra. y = mx + b y - b = mx (y-b)/m = x
Just subtract y from both sides. 'm' becomes 'A', 'b' becomes 'C' and 'B' will be equal to one.
It is an arbitrary convention.
It depends on what you are trying to solve for. Here is a solution for x... y = mx + b y - b = mx (y - b) / m = x Note: If m is zero, then there is no solution, because the line is horizontal
The equation y = mx + b is the equation for a line in slope intercept form, with m being the slope, and b being the y-axis intercept.
In the equation y = mx + b, x is the independent variable.Also, m is the slope, b is the y-intercept, and y is the dependent variable.
m = the slope of the line. rise/run. Y2 - Y1/X2 - X1
m = slope b = y intercept ( value when x =0)
The x-intercept is equal to -b/m.
The value of m is the slope and the value of b is the y intercept.
That depends on the values of m and b because it is the formula for a straight line equation whereas m is the slope and b is the y intercept
Not quite. 'm' is the slope of the line. 'b' is the y-intercept The x-intercept is ( -b/m ).